Construções com o verbo ter em documentos escritos por redatores inábeis no século xx - Silva, Jalmir Profeta da (2025)
This dissertation proposes, based on the constructional approach of cognitive-functional grammar, a description and analysis of the schemes that integrate the verb ter in documents written by unskilled writers in the 20th century, in order to characterize the uses of constructions with the aforementioned verb in texts written by unskilled handwriting, believing that such discussion may reveal partial aspects of the constructicon of users with the selected profile. For this purpose, 103 realizations of constructions with the verb ter that materialized in documents written by unskilled writers were analyzed. The corpus for analysis and description was collected from a collection consisting of 131 letters, whose writers are rural residents of the municipalities of Riachão do Jacuípe, Conceição do Coité and Ichu, in the semi-arid region of Bahia, who are adults in the initial phase of acquiring writing skills (Marquilhas, 2000). The development of this research is guided by the work agenda of the Electronic Corpus of Historical Documents of the Sertão (CE DOHS/UEFS), as well as the CONHPOR project - Historical Constructionary of the Portuguese Language: morphological and syntactic schemes of Portuguese in constructional, relational and cognitivist approaches. The theoreticalmethodological framework is based on authors who deal with both the foundations of Construction Grammar from a cognitive-functional perspective and important aspects for a socio-historical approach to the Portuguese language, thus, the following stand out: Goldberg (1995, 2006), Pinheiro (2016), Santiago (2019), Barbosa (2017), Chiavegatto (2009), VIotti (1998), Pinheiro (2009), Peixoto (2012), Vieira (2017) and Costa (2018). Once the research was developed, it was possible to verify the occurrence of five constructions: (i) metaphorical possession (“Farsa um tudo purmin detas que nois ten tempo para Acerta”), (ii) completed action (“Compadi pitanga I was satisfied that the gentleman had come to me”), (iii) possession (“and I will tell you that the chicken I have there is the one that belonged to Bernadete”), (iv) existential construction (“let me apologize for the mistakes you have and receive a reminder”) and (v) obligatory construction (“Good Pitanga if you didn’t sell the donkey you don’t have to sell it because I’m going to send it to be stolen in September”). The results of this research reveal that, in the uses of the item ter in documents written by unskilled writers in the 20th century, there is a predominance of more abstract uses, in which it appears mainly as a full verb, auxiliary verb and support verb, which demonstrates the high abstraction of this element, but also varied types of constructions.